Correction: Development of a bio-electrospray system for cell and non-viral gene delivery. Issue 20 (16th March 2018) - Lee, Myung Chul; Seonwoo, Hoon; Garg, Pankaj; Jang, Kyoung Je; Pandey, Shambhavi; Kim, Hong Bae; Park, Sang Bae; Ku, Jong Beom; Kim, Jang Ho; Lim, Ki Taek; Chung, Jong Hoon
Abstract : Correction for 'Development of a bio-electrospray system for cell and non-viral gene delivery' by Myung Chul Lee et al., RSC Adv., 2018, 8, 6452–6459.